Ammonia production from algae via integrated hydrothermal gasification, chemical looping, N2 production, and NH3 synthesis. (1st May 2019) - Wijayanta, Agung Tri; Aziz, Muhammad
Abstract: Novel integrated system to convert algae to NH3 is proposed with the objective of effective and thorough energy/heat circulation to achieve high total energy efficiency. The integrated system mainly consists of hydrothermal gasification (HTG), chemical looping, N2 production, NH3 synthesis, and power generation. Algae are converted initially to syngas through HTG, which is further converted to CO2 and H2 in chemical looping module. The produced H2 from chemical looping module is reacted with the produced highly-pure N2 from N2 production module to form NH3 in NH3 synthesis module. To realize high energy-efficiency, an enhanced process integration, which simultaneously integrates both exergy recovery and process integration technologies, is applied. Therefore, the energy/heat involved in the integrated system is recirculated thoroughly and used partly for power generation. Macro alga of Cladophora glomerata (Chlorophyta) is used as the sample in the study. The effects of temperature and algae-to-water mass ratio during HTG are evaluated in terms of their influence to the total energy efficiency. From process modeling and calculation using SimSci Pro/II, the proposed integrated-system shows relatively high total energy efficiency of about 38%, including both NH3 and power production, achieved at HTG temperature of 380 °C and mass ratio of 0.01. Highlights: Novel integrated system to effectively convert algae to NH3 is proposed. It consists of gasification, chemical looping, N2 production and NH3 synthesis. Hydrothermal gasification is employed for higher conversion and efficiency. Relatively high total energy efficiency of about 38% can be achieved.